EPISODIC CONTINENTAL GROWTH AND SUPERCONTINENTS: A MANTLE AVALANCHE CONNECTION? - Condie K.C. (My University, 1998)
Episodic growth of continental crust and supercontinents at 2.7, 1.9, and 1.2 Ga may be caused by superevents in the mantle as descending slabs pile up at the 660-km seismic discontinuity and then catastrophically sink into the lower mantle. Superevents, in turn, may comprise three or four events, each of 50-80 My duration, and each of which may reflect slab avalanches at different locations and times along the 660-km discontinuity. Superplume events in the late Paleozoic and Mid-Cretaceous may have been caused by minor slab avalanches as the 660-km discontinuity became more permeable to the passage of slabs with time. The total duration of a superevent cycle decreases with time reflecting the cooling of the mantle.
Keywords: CONTINENTAL CRUST; MANTLE; PLATE TECTONICS; MODELS; SLABS